Diagnostic Accuracy of Doppler Scan of Portal Vein to Determine Early Cirrhosis of Hepatitis-C Patients in Gujranwala Population - Mian Waheed Ahmad, Nawaz Rashid, Iqbal Hussain Dogar, Muhammad Umer, Hafiza Sameeya Shehzadi, Rameez Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of study is to establish accuracy of doppler sonography in diagnosis of early cirrhosis in hepatitis C positive patients, which is based on portal vein velocity and resistive index considering Histopathology as a gold level standard Student Design: It was a cross sectional comparative study (validation study). Place & Duration of Study: The student was held in Radiology department of District Headquarter Teaching Hospital Gujranwala from 1st July 2019 to 30th June 2020. Materials and Methods: The calculated sample size was 50 cases of anti-HCV anti bodies positive on their blood test fulfilling the inclusion criteria were examined for color Doppler ultrasound to see direction and average blood flow in the portal vein. All these cases were undergone core biopsy of liver and histopathology carried out. The results of histopathology were taken as superior quality / gold standard. Results: Mean age of the patients was found to be 42.5 years. The frequency of the hepatitis C in the different age group varied. Out of the 50 about 37 patients (74%) show decrease in the portal vein velocity towards lower limits regardless no ultrasonic appearance of the cirrhosis and remaining 13 patients (26%), show normal velocities towards upper limits. According to this study portal vein velocity in early cirrhosis is between 10-16 cm/sec and these initial cirrhotic changes confirmed on core liver biopsy (gold standard). Sensitivity was found to be 94.4%, specificity 78.5%, diagnostic accuracy 90.0%, both the NPV (negative predictive value) and PPV (positive predictive value) are high (NPV: 78.5%). Practical Implication: To best of our knowledge, there is very little information on this research topic in our area. The design of improved medical strategies to handle such situations and the improvement of their management will be made possible by the availability of such evidence. Conclusion: In our study, the maximum patients (38%) were suffering with this disease for more than 7 years but less than 9 years. 74% patients showed a decrease in the portal vein velocity towards the lower limit, and 26% patients showed normal velocity towards the upper limit. Keyword: Portal Vein, Doppler Ultrasound, Anti HCV, Core Liver Biopsy, Histopathology, Hepatitis C